Caged Compounds: A Novel Synthesis of Homocubane and its Analogues and Gold-(I) Catalysed Propargylation of Azinium Salts - Smithson, Jack (2025)
We disclose a novel synthetic method to access the homocubane ester 4a in 4 steps, in an overall yield comparable or superior to literature methods. The sequential transformations of a [6+2] cycloaddition, 4π electrocyclisation, followed by a dehydrogenation and [2+2] cycloaddition displays the relatively simple route to access this challenging to make structure. We also inadvertently synthesised an interesting polycyclic structure we have tentatively assigned as formal [4+2] product 6.